2019
DOI: 10.1155/2019/7276230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Onchocerciasis and Associated Factors among Adults Aged ≥ 15 Years in Semen Bench District, Bench Maji Zone, Southwest Ethiopia: Community Based Cross-Sectional Study

Abstract: Background. Though onchocerciasis control and elimination through community directed treatment with ivermectin were conducted for the last fifteen years, prevalence of onchocerciasis and factors associated with it in the study area are yet not known. The aim of the current study is to assess prevalence of onchocerciasis and associated factors among adults aged greater than or equal to fifteen years in Semen Bench district, Bench Maji zone, southwest Ethiopia: community based cross-sectional study 2018. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
5
12
0
Order By: Relevance
“…Similar findings were reported from other endemic areas where at least 14 rounds of MDA was carried out in Africa [45,[49][50][51][52][53][54] and Latin America [55]. In contrast, irrespective of long term CDTi, considerably higher prevalences than the present finding were reported from other CDTi implementation areas in Africa [29,[56][57][58][59][60][61][62]. Several factors may have contributed to the differences in the impact of CDTi.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings were reported from other endemic areas where at least 14 rounds of MDA was carried out in Africa [45,[49][50][51][52][53][54] and Latin America [55]. In contrast, irrespective of long term CDTi, considerably higher prevalences than the present finding were reported from other CDTi implementation areas in Africa [29,[56][57][58][59][60][61][62]. Several factors may have contributed to the differences in the impact of CDTi.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, in this study, living around river basin was an independent determinant for CLTI adherence. A kind of community living condition therefor, increased utilization of annual treatments with ivermectin, as likely supported by findings conducted elsewhere [4,32,39]. Fast flowing river water bed is the commonest suitable ecological zone in which flies are harbored and breed.…”
Section: Discussionsupporting
confidence: 55%
“…In endemic localities of RB, communities' hesitation to inhabit and dwell around fertile riverside (bank) is linked with black fly infestation [37][38][39]. Likewise, in this study, living around river basin was an independent determinant for CLTI adherence.…”
Section: Discussionmentioning
confidence: 49%
“…Even though the Federal Ministry of Health of Ethiopia had set a goal to eliminate onchocerciasis and to stop community-directed treatment with ivermectin by the end of 2020, it was shifted to 2025 due to the potential transmission of the disease in the endemic areas [ 13 ]. In our study area, the Bench Maji Zone, the annual and the biannual community-directed treatment with ivermectin (CDTI) to control and eliminate the disease were started in 2003 and 2013, respectively; however, the prevalence study done in the area showed that the disease prevalence was still 6.32% [ 8 ]. Even though the aforementioned community-directed treatment with ivermectin (CDTI) was proven effective in treating the disease, the level of compliance to the treatment was not well addressed in our study area.…”
Section: Introductionmentioning
confidence: 99%
“…The 2019 and the 2020 WHO report, respectively, showed that more than 99% and more than 80% of the infected cases live in 31 African countries [1,2]. Different studies done in Ethiopia showed that the disease is still more prevalent in western and southwestern parts of the country with the prevalence range of 6.32% in the Bench Maji Zone to 31.3% in indigenous communities of Assosa [7][8][9].…”
Section: Introductionmentioning
confidence: 99%